Toll-Like Receptor Signalling Pathways and the Pathogenesis of Retinal Diseases - Titi-Lartey, Owuraku; Mohammed, Imran; Amoaku, Winfried M. (Frontiers in Ophthalmology, 2022)
There is growing evidence that the pathogenesis of retinal diseases such as diabetic retinopathy (DR) and age-related macular degeneration (AMD) have a significant chronic inflammatory component. A vital part of the inflammatory cascade is through the activation of pattern recognition receptors (PRR) such as toll-like receptors (TLR). Here, we reviewed the past and current literature to ascertain the cumulative knowledge regarding the effect of TLRs on the development and progression of retinal diseases. There is burgeoning research demonstrating the relationship between TLRs and risk of developing retinal diseases, utilising a range of relevant disease models and a few large clinical investigations. The literature confirms that TLRs are involved in the development and progression of retinal diseases such as DR, AMD, and ischaemic retinopathy. Genetic polymorphisms in TLRs appear to contribute to the risk of developing AMD and DR. However, there are some inconsistencies in the published reports which require further elucidation. The evidence regarding TLR associations in retinal dystrophies including retinitis pigmentosa is limited. Based on the current evidence relating to the role of TLRs, combining anti-VEGF therapies with TLR inhibition may provide a longer-lasting treatment in some retinal vascular diseases.